Pengembangan Desa Smart Farming Melalui Inovasi Pupuk Organik Cair - Bhaga Aninditatama; Agus Setiawan; Agus Mutia; Firjatullah Putra Ramadhan; Anita Ardiansyah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The liquid organic fertilizer (POC) production training in Ngadirejo Village, Widang Subdistrict, Tuban Regency, was conducted to reduce farmers’ dependence on chemical fertilizers and promote sustainable agriculture. The program actively engaged farmers through lectures, hands-on practice, discussions, and skill evaluations. POC was produced from local organic waste such as water hyacinth, banana corms, moringa leaves, cow urine, and fish meal, fermented for 14–30 days. The final product contains complete nutrients to improve soil fertility and crop productivity while being environmentally friendly. The training results indicated an increase in community knowledge and skills to independently produce POC. This innovation has the potential to support smart farming practices and enhance farmers’ welfare.